Dental caries and children's weights. Issue 1 (March 1982) - Miller, J.; Vaughan-Williams, E.; Furlong, R.; Harrison, L.
Abstract : The weights of 1105 children who needed the extraction of deciduous teeth under general anaesthesia were significantly lighter than the weights of 527 children who did not have dental extractions. Dietary analysis was made for 204 children after extraction and 131 children of the non-extraction group. Children who require multiple extractions before the age of 6 may be suffering an undetected malnutrition.